Implementation of Character Education at The Elementary School Level - Diharja, Umar; Hadiwinarto, Hadiwinarto (Universitas Pahlawan Tuanku Tambusai, 2021)
Education has a major role in building and shaping the quality of character of the nation's children. The purpose of this study is that researchers want to identify the characters shown by SDIT Mutiara Cendekia students and describe the application of character education. The research method used is the descriptive qualitative research method, so the results of this study are: 1) Character values that are applied and shown are religious, independent and responsible, honest and wise, respectful and polite, generous, and helpful. 2) The application and concept of character education at SDIT Mutiara Cendekia by cultivating or habituation. 3). Strategies used by teachers in implementing character education such as always reminding students of good things, giving educative warnings and punishments, teachers providing examples or being role models, applying habituation, and growing awareness and desires of individual students. 4) Barriers to the implementation of character education at SDIT Mutiara Cendekia include factors from teachers, parents, the environment, and the students themselves.